Dual Feuerbach Theorem in an Isotropic Plane - Kolar-Šuper, Ružica; Kolar-Begović, Zdenka; Volenec, Vladimir (Sarajevo Journal of Mathematics, 2024)
The dual Feuerbach theorem for an allowable triangle in an isotropic plane is proved analytically by means of the so-called standard triangle. A number of statements about relationships between some concepts of the triangle and their dual concepts are also proved. 2000 Mathematics Subject Classification. 51N25